The Mediating Role of Metacognitive Awareness on the Relationship Between Teacher Classroom Assessment and Self-Regulated Learning in Secondary School Students - Moradi, Shokoufeh; Yousefi Afrashteh, Majid (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the mediating role of metacognitive awareness in the relationship between teacher classroom assessment and self-regulated learning (SRL) among secondary school students. A correlational research design with a quantitative approach was employed, involving 351 secondary school students in Zanjan city, Iran. Data were collected using three standardized questionnaires: the Teacher Classroom Assessment Questionnaire, the Metacognitive Awareness Questionnaire, and the Self-Regulated Learning Questionnaire. The sample was selected through convenience sampling, and data analysis included descriptive statistics, Pearson correlation, and path analysis using SPSS-26 and LISREL software. The results revealed that teacher classroom assessment had a significant direct effect on both metacognitive awareness (β = 0.568, p < 0.001) and SRL (β = 0.553, p < 0.001). Additionally, metacognitive awareness mediated the relationship between teacher classroom assessment and SRL, with an indirect effect of β = 0.159 (p < 0.001), indicating its role as a mediating mechanism. The study highlights the critical role of metacognitive awareness in linking teacher classroom assessment to SRL, providing insights for educators to design assessments that promote self-reflection and metacognitive development. By enhancing metacognitive awareness, teachers can effectively support students in becoming self-regulated learners, ultimately improving academic outcomes and lifelong learning skills.